ROLE OF EDUCATIONAL CLUSTER IN EDUCATION AND EMPLOYMENT (American Journal of Pedagogical and Educational Research, 2025)
This article scientifically and theoretically covers the strategies of an educational cluster in the organization of a production and educational cluster, the conditions and scientific factors for the effective development of an educational cluster, as well as the main goals of an educational cluster.